The emergence of the English native speaker : a chapter in nineteenth-century linguistic thought - Hackert, Stephanie (Language and Social Processes LSP., 2012)
The volume reconstructs the coming-into-being of the English native speaker in the second half of the nineteenth century in order to probe into the origins of the problems surrounding the concept today. A corpus of texts which includes not only the classics of the nineteenth-century linguistic literature but also numerous lesser-known articles from periodical journals of the time is investigated by means of historical discourse analysis in order to retrace the production and reproduction of this particularly important linguistic ideology.